Sustainable Consumption, Promise or Myth? Case Studies from the Field - Jean Leon Boucher; Jukka Heinonen (Cambridge Scholars Publishing, 2019)
This book brings together a number of recent case studies from the broad field of sustainable consumption. As they evaluate the promises, myths, and critiques of sustainable consumption, these essays can also be categorized into a range of different societal perspectives, from the individual to collectivities.The first chapters explore the personal consumer, discussing how individual consumptive choices relate to lifestyle and culture, and how choices are reflected in the carbon footprints of consumers and vehicles like the automobile.